Synthesis and Characterization of Palm Oil-Based Resin For UV Coating - Cheong, Mei Yee (2006)
The production of UV curable acrylated polyol esters fiom palm oil and its downstream products offers potential and promising materials for a number of applications such as polymeric film preparation and wood coatings. in this study, palm olein-based polyol of ethylene glycol was reacted with acrylic acid in the presence of a catalyst and inhibitors via condensation esterification process at various temperatures (70.0, 80.0, 90.0 or 100.O°C), stirring speed of 100 or 400 rpm and under vacuum for 15 hours. The reaction temperature of 80.0°C and the stirring rate of 400 rpm produce a homogeneous product. Optimizations for the synthesis were also carried out using a catalyst concentrations ranging fiom 0.0 to 5.0% of polyol weight.Fifteen different formulations have been investigated using the synthesized prepolymers with monomers and a small amount of photoinitiator. Monomers used were 1,6-hexanediol diarylate (HDDA) and trimethylolpropane triacrylate W T A ) while photoinitiator used was l-hydroxy cyclohexyl phenylketone (Irgacure 184). The mixtures were cured to make thin polymeric films under W radiation with doses between 2 to 14 passes (energy per pass is 0.600 ~lcm~C)o.a ting and curing was carried out on glass for pendulum hardness characterization, haziness and scratch measurement as well as FT-IR analysis. Coating and curing were done on rubber wood for cross hatch adhesion test. Pendulum hardness 'of the film prepared h m the UV curable formulation with monomer HDDA and the prepolymer prepared using 3% catalyst was 24.5%. The radiation dose was 14 passes. The highest pendulum hardness of 49.4% was achieved when using WV curable formulation with monomer TMPTA and the prepolymer prepared using 2% catalyst. The radiation dose needed was 10 passes. Formulation of UV curable coating using the optimized aaylated polyol ester prepolymer and monomer TMPTA exhibited higher scratch measurement and lower haziness compared to those of the formulation with monomer HDDA UV curable formulation of prepolymer with monomer HDDA gave better adhesion on rubber wood than that of with monomer TMPTA Films cured by W radiation made from prepolymexs on both $ass panel and rubber wood surfaces showed good hardness, scratch resistance and adhesion with almost clear transparency. In general, it can be conchided that newly synthesized UV radiation curable palm-based acrylated polyol ester prepotymers are promising candidates for wood coating applications.